Starch as a potential fat replacer for application in cheese: Behaviour of different starches in casein/starch mixtures and in the casein matrix - Diamantino, Vivian R. [UNESP]; Costa, Mariana S. [UNESP]; Taboga, Sebastião R. [UNESP]; Vilamaior, Patrícia S.L. [UNESP]; Franco, Célia M.L. [UNESP]; Penna, Ana Lúcia B. [UNESP] (Elsevier, 2019)
The behaviour of different types of native starch (regular, waxy, and high-amylose maize starch) and modified starch (acetylated/adipate maize starch with regular basis and hydroxypropylated/phosphate maize starch with waxy basis) in mixtures with calcium caseinate (CN) and embedded in casein matrix were studied to understand the potential use of starch as a fat replacer in fresh cheese. In mixtures with CN, the modified starches showed high viscosities (peak and final), indicating high potential for water retention in cheese, as well as low peak temperature and low variation of enthalpy (ΔH), requiring thereby low gelatinisation temperatures. They also showed low tendency for retrogradation, high swelling power, and good thermomechanical resistance. Furthermore, due to the very low loss in whey of both modified starches and their presence embedded in the protein matrix acting as inert fillers, they can be considered as promising fat replacers in cheese.